Analisis ANALYSIS OF THE USE OF DIGITAL EDUCATIONAL GAMES IN DEVELOPING THE LANGUAGE OF CHILDREN AGED 4–5 YEARS - Elsa Yuliani; Tasya Etriani; Mesy Agustiani; Marma Safitri; Umi Nistira; Putri Patrika; Amanda Maharani (Universitas Darunnajah, 2026)
The development of digital technology has significantly influenced early childhood education, including the use of digital educational games as a medium for language development. This study aims to analyze the use of digital educational games in developing the language skills of children aged 4–5 years, covering aspects of expressive and receptive language. This research employs a literature review (studi literatur) method by collecting, reviewing, and synthesizing relevant scientific articles published between 2016 and 2024. Data sources were obtained from national and international journals, including Jurnal Obsesi, Murhum, KIDDO, and PAUD Agapedia. The results show that digital educational games have a significant positive effect on children's language development, especially in improving vocabulary, listening skills, and verbal expression. Interactive elements such as animation, audio narration, and responsive feedback were identified as key factors in stimulating language acquisition. This review also found that the effectiveness of digital games depends on the appropriateness of content with the child's developmental stage and the role of educators in guiding the learning process. The findings of this study confirm that digital educational games are a relevant and effective innovative media for language development in early childhood.